Relation between insulin secretory capacity and microangiopathy in young diabetic patients in Bangladesh - Subhan, SS; Bhuiyan, ZI; Akter, K; Goswami, MK; Rahman, HS; Ali, L (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jan;16(1):1-6.The abstract of this article is available on the PubMed website